Social and Environmental Shareholder Activism in the Public Spotlight: US Corporate Annual Meetings, Campaign Strategies, and Environmental Performance, 2001-04. - Clark, G; Salo, J; Hebb, T (Pion Ltd., 2008)
Held in abeyance by the Cold War and the preeminence of the nation-state over the past fifty years, the legitimacy of the corporation is once again in dispute. New kinds of private agencies and social actors have emerged to raise questions and, in some cases, intervene directly in the governance of major corporations. Often, corporate engagement is out of the public view-being a conversation amongst financial elites about common interests. In other cases, however, shareholder activism is a public affair played out in the full glare of the media at annual general meetings. In this paper social activists' corporate engagement strategies are evaluated utilizing three proprietary databases which enable analysis of the patterns of activists' shareholder resolutions with respect to the financial structure and environmental performance of target corporations. An analytical framework is introduced, referencing two models of the firm, the nature of corporate assets (tangible and intangible), and public expectations of corporate performance. Utilizing Interfaith Center for Corporate Responsibility data on social activists' shareholder resolutions it is shown that these types of resolutions can be differentiated according to the nature and volume of activists' resolutions and the motive forces driving intervention. It is also shown that, for all the differences between institutional investors and social activists, they may share the same approach to realizing shareholder value depending on the nature of the corporation.